2021
DOI: 10.1002/ecs2.3317
|View full text |Cite
|
Sign up to set email alerts
|

Are bison movements dependent on season and time of day? Investigating movement across two complex grasslands

Abstract: The American plains bison (Bison bison) is an iconic herbivore on North American grasslands, yet many questions surrounding their basic biology remain unanswered. We analyzed fine-resolution movement data (12 minute) from two of the largest remaining prairie tracts in the Great Plains of North America to address whether bison movement and distance travelled are affected by seasonal or diurnal rhythms. We fit binomial movement and movement distance data to generalized linear mixed models to test whether site, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 36 publications
(71 reference statements)
1
21
1
Order By: Relevance
“…Furthermore, this pattern was consistent across all sites suggesting a broad‐scale response to seasonal rhythms. This is contrary to previous research that found that bison at different sites moved differently during the fall, which McMillan et al (2021) suggested was caused by topographical differences between these sites. Seasonal rhythms appeared to influence bobwhite net displacement the most during spring.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Furthermore, this pattern was consistent across all sites suggesting a broad‐scale response to seasonal rhythms. This is contrary to previous research that found that bison at different sites moved differently during the fall, which McMillan et al (2021) suggested was caused by topographical differences between these sites. Seasonal rhythms appeared to influence bobwhite net displacement the most during spring.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, our ability to collect movement data at fine‐temporal scales was limited by VHF telemetry. Given the technological advancements in telemetry and accessibility of GPS technology, scientists and managers are now able to better understand movement patterns at fine‐temporal scales (Cagnacci et al, 2010; McMillan et al, 2021). In fact, GPS technology has significantly increased our understanding of how diel and seasonal rhythms affect movements of large mammals and large birds (Cagnacci et al, 2010; McMillan et al, 2021; Owen‐Smith & Goodall, 2014; Zavalaga et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations